PERANAN SATUAN KERJA PENGAWASAN SUMBER DAYA KELAUTAN DAN PERIKANAN DALAM PEMBERANTASAN TINDAK PIDANA PERIKANAN DI WILAYAH PENGELOLAAN PERIKANAN KOTA BATAM PROVINSI KEPULAUAN RIAU - Permana, Adi; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The term maritime countries to the Republic of Indonesia because the sea area reached 3,257,483 km2, almost two-thirds of the territory of Indonesia is an ocean. This geographical condition underlining the potential for enormous natural in the field of fisheries. Indonesia itself has implemented a regulation of fisheries policy by issuing Law No. 45 of 2009 Juncto Law Number 31 Year 2004 on Fisheries. Currently, the implementation of the management, utilization, and surveillance has not run optimally, due to rampant cases of crimes and violations of fisheries in WPPRI is not only done by Indonesian fishing vessels, but also to foreign fishing vessels. It is a challenge for law enforcement to Batam SATKER PSDKP fisheries. The purpose of this research, First, the role of SATKER Knowing PSDKP in the eradication of the fisheries in the area of fisheries management. Second, On Obstacles SATKER PSDKP in the eradication of the fisheries in the area of fisheries management. Third, to know what efforts were made by SATKER PSDKP in overcoming barriers to the eradication of the fishery. This type of research is a sociological study, where this research look at the correlation between law and society using interviews in PSDKP Base Batam and literature study. From the results of research can be concluded. The first role of SATKER PSDKP in the eradication of fishery namely monitoring, control, surveillance and enforcement including implementation of VMS, published SLO, patrolling, socialization and community development, received the report, verify fishing vessel, and conduct investigations. Second, barriers Satker PSDKP Batam related eradication of fishing among others lack of quality quantity of infrastructure, budget and human resources, the condition of the region broad oversight and erratic weather in the conduct of supervision, lack of public awareness, ineffective coordination between law enforcement fishery and the lack of participation of other countries in the fight against the crime of fisheries. Third, efforts are being made to overcome these barriers is to increase the competence and quantity of personnel and infrastructure, fostering awareness of the law for the public and coordination between law enforcement agencies and by conducting a deterrent effect did the bombing of the ship. Suggestions Author, First SATKER PSDKP Batam City needs to improve oversight and prosecution of all perpetrators of criminal acts. Second, to overcome these obstacles must take steps to improve the performance of accurate internal and coordination. Third, efforts to overcome these barriers should be further enhanced by measures that are more accurate and integrated. Keyword: Role-SATKER PSDKP-Eradiction-Crime Of Fisheries